2004
DOI: 10.1080/14767050410001725578
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino acid concentrations throughout normal pregnancy and early stages of intrauterine growth restricted pregnancy

Abstract: Levels of most maternal amino acids decrease and some increase during early gestation reflecting a metabolic adaptation that occurs in normal pregnancies. Pregnancies that later develop IUGR show a lack of these adaptations for a significant number of both essential and non-essential amino acids, suggesting a lack of adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 16 publications
11
23
0
Order By: Relevance
“…Our previous studies pointed to certain relationship between the amino acid levels in the blood plasma and brain [23], which may be used for translation of findings on the brain samples in animal models to human studies. For instance, increased content of tryptophan in cerebellum of pregnant rats, shown in our study (Table 1) corresponds to the findings in humans, which indicate that in maternal plasma, tryptophan catabolites and related compounds change in pregnancy [38,39]. This study suggests the neurotransmitters-dependent adaptation of maternal body to the fetus growth.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous studies pointed to certain relationship between the amino acid levels in the blood plasma and brain [23], which may be used for translation of findings on the brain samples in animal models to human studies. For instance, increased content of tryptophan in cerebellum of pregnant rats, shown in our study (Table 1) corresponds to the findings in humans, which indicate that in maternal plasma, tryptophan catabolites and related compounds change in pregnancy [38,39]. This study suggests the neurotransmitters-dependent adaptation of maternal body to the fetus growth.…”
Section: Discussionsupporting
confidence: 88%
“…Changes in plasma concentration of amino acids may play an important role in determining appropriate fetal growth. Consistent with reported changes in several amino acids found in pregnant mother (Di Giulio et al, 2004), many kinds of amino acids also demonstrated different degrees of deletion in our study. The decreased concentrations of some metabolites such as N-acetyl glycoprotein, creatine and creatinine related to the decomposition of the protein (Delanghe et al, 1989;Pinto et al, 2015).…”
Section: Protein Metabolismsupporting
confidence: 81%
“…It is thought that this indicates impaired uteroplacental adaptation to pregnancy, which may be an early step in the development of the condition. 14 The lower fetal amino acid concentrations in IUGR pregnancies are most probably the result of reduced transplacental transport. Several studies in both humans 15 16 and sheep 17 18 have shown lower in vivo placental transport of labelled amino acids in IUGR pregnancies than in AGA pregnancies.…”
Section: Fetal Growth and Metabolismmentioning
confidence: 99%